Grain weight retention during terminal heat stress in hard winter wheat - Schuh, Nicholas J. (Kansas State University, 2024)
Climate-resilient wheat cultivars with tolerance to high temperatures after flowering are essential to reliable wheat production in the central and southern Great Plains. Breeders have an experiential understanding of germplasm capable of maintaining test weight under terminal heat stress, yet understanding of underlying genetics is limited. In a preliminary greenhouse/growth chamber experiment to identify post-anthesis heat stress tolerance genetic resources within central and southern Great Planes germplasm, two breeding lines were identified with contrasting tolerance phenotypes: HV9W03-1596R maintained green leaf area, and TX04M410164 maintained grain weight under post-anthesis heat stress. A recombinant inbred population (208 lines) was developed from the progeny of crossing these two lines and grown in ten Kansas field environments. Traits measured were yield, plant height, flowering time, physiological maturity time, grain fill period, test weight, kernel diameter, kernel weight, and kernel hardness. Yield, plant height, flowering time, test weight, kernel diameter, and kernel weight were all found to be highly heritable. In the 2018 field season, average high temperature during the 21 days following anthesis at three trial locations was 29.1°C to 30.4°C, while the optimal temperature for wheat grain filling is reported to be 21.3°C. In three 2018 trial locations, mean test weight ranged from 652 to 758 g L⁻¹, and mean kernel weight ranged from 19.8 to 23.5 mg. In contrast, in three 2020 trial locations, mean test weight ranged from 745 to 830 g L⁻¹, and mean kernel weight ranged from 26.5 to 30.9 mg. Stress sensitivity indices (SSIs) were calculated at seven trials, using three highest yielding trials as the control environment. The SSIs for flowering time and physiological maturity had very little variation under an extreme stress environment and high variation under a moderately stressful environment. We observed the same phenomena in yield and kernel diameter SSIs. Two quantitative trait loci were found on chromosome 1B in a preliminary analysis, and SNP markers were developed. One SNP was significant for kernel diameter, kernel hardness, kernel weight, test weight, grain yield, plant height, and grain fill period length and the other was significant for kernel hardness, test weight, grain yield, plant height, and grain fill period length best linear unbiased predictors. One SNP was significant for kernel diameter and test weight stress sensitivity, and the second SNP was significant for kernel weight, grain fill period, and physiological maturity stress sensitivity. The RIL population also was segregating for the Ppd-D1 and Vrn-D3 genes that affect flowering time. These flowering time genes had significant effects on stress sensitivity. Future work will isolate near isogenic lines from RILs heterozygous at one or both of the 1B regions. These lines will be evaluated for heat tolerance in controlled environments and field environments to quantify the effects of these regions on post anthesis heat stress tolerance.
Keywords: Wheat; Plant breeding; Heat stress